Miscanthus sinensis 'Purpurascens' 'Purpurascens’ Japanese Silver Grass - Edward Gilman (EDIS, 2007)
This document provides an overview of Miscanthus sinensis ‘Purpurascens’, commonly known as maiden grass or flame grass. It describes the plant’s physical characteristics, including its height, spread, and distinctive reddish-purple fall color. The document highlights its uses in landscaping, such as mass planting, borders, and as an accent plant. It also covers the plant’s growth requirements, including its preference for full sun and well-drained soils, as well as its moderate drought tolerance. Additionally, the document mentions the plant’s invasive potential and the absence of serious pest issues. Original publication date September 1999.